The Nehru-era economic history and thought & their lasting impact - Panagariya, Arvind (New York Oxford Univ. Press, 2024)
"Economists and policy analysts can influence economic-policy outcomes at various levels. Those directly employed in the government can influence their other bureaucratic colleagues and politicians. They serve on important committees appointed to recommend solutions to specific policy problems. Reports of these committees can effectively strengthen the existing regime or inject new ideas for change. Economists and policy analysts outside the government can influence the thinking of politicians and bureaucrats through their writings, speeches, and media interviews. But they also influence broader public opinion. As educators in academic institutions, they shape the thinking of future generations"--
Includes bibliographical references and index.
Keywords: Nehru, Jawaharlal, -- 1889-1964.; India -- Economic conditions -- 1947-; India -- Economic policy; India -- Politics and government -- 1947-